Effects of over-scheduled children: perspectives of childcare workers - Kringen, Erin M.; Nagel, Amanda K. (University of Wisconsin--Stout. Research Services, 2006)
This study used survey research to gather the University of Wisconsin-Stout Child and Family Study Center (CFSC) childcare workers’ perspectives regarding the effects of over- scheduling children in Menomonie,Wisconsin.The participants in this study were eight individuals who were undergraduate students or had completed their undergraduate education and six individuals who were graduate students or who had completed their graduate education. The computer program Statistical Package for Social Sciences (SPSS) was used to statistically analyze the data by use of frequencies,cross-tabulations,and mean comparisons. Our findings indicate that childcare workers do not perceive children as being over-scheduled. Another finding was that there might have been a gap in the education on over-scheduled children for the staff of the CFSC. Future research could include duplicating this same survey in a larger and more diverse population with childcare workers and teachers.
Keywords: over-scheduled children; stress; day care providers; Child care workers; Student activities